Influence of urban canopy green coverage and future climate change scenarios on energy consumption of new sub-urban residential developments using coupled simulation techniques: A case study in Alexandria, Egypt - M. Fahmy; M. Mahdy; S. Mahmoud; M. Abdelalim; S. Ezzeldin; S. Attia (Energy Reports, 2020)
The trend of urban and suburban developments is concluding that more than 70% of the world population will be living in urban areas by mid-21st century within dis-comfortable built environment. In Egypt, a concern about climate change resilient communities is having more listeners after Paris climate agreement in 2015. Therefore, assessing present and future outdoor microclimatic effects on the indoor environmental quality and energy consumption in turn is crucial to build the capacities for mitigation and adaptation strategies. In this research work, the coupled outdoor-indoor simulation methodology is applied using ENVI-met and DesignBuilder to let buildings respond to the street canyon conditions since indoor simulation packages does not consider urban details. Such mutual relation is explored in a site case in Borg El-Arab, Alexandria, Egypt, in which urban canopy green coverage (trees, green walls and roofs) have been applied. Comparing results of indoor thermal comfort for the examined site buildings in present until end of century (2020, 2050 and 2080) with and without the urban canopy green coverage; show that indicators and adaptation strategies can be developed for climate change scenarios.
Keywords: 330; Climate change; Environmental performance; Canopy green coverage; Coupled simulations